2020
DOI: 10.1089/cap.2019.0133
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of AR19, an Immediate-Release Amphetamine Sulfate Formulation Designed to Deter Manipulation for Administration Via Nonoral Routes: Bioequivalence to Reference Racemic Amphetamine Sulfate, Dose Proportionality, and Food Effect

Abstract: Objectives: We evaluated the pharmacokinetics (PK) of an investigational immediate-release amphetamine (AMP) sulfate formulation (AR19) designed to deter nonoral administration versus reference racemic amphetamine sulfate (RA-AMPH). We investigated AMP bioavailability from AR19, the effect of taking AR19 with food or sprinkling the capsules on food, and dose proportionality. Methods: Participants received AR19 (20 mg) or reference RA-AMPH (20 mg) (bioequivalence study) or AR19 5 or 30 mg (dose comparison study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
2
2
1
Order By: Relevance
“…As already observed with the forensic serum samples, also in this experiment, higher concentrations of dexamisole than of levamisole are present at all time points. This is in contrast to observations for amphetamine 43,46 and 4‐FA, 17 where (R)/(S)‐ratios <1 were observed in the absorption phase. On the other hand, for MDMA, (R)/(S)‐ratios were >1 at any time as well 16,41,42 .…”
Section: Discussioncontrasting
confidence: 99%
“…As already observed with the forensic serum samples, also in this experiment, higher concentrations of dexamisole than of levamisole are present at all time points. This is in contrast to observations for amphetamine 43,46 and 4‐FA, 17 where (R)/(S)‐ratios <1 were observed in the absorption phase. On the other hand, for MDMA, (R)/(S)‐ratios were >1 at any time as well 16,41,42 .…”
Section: Discussioncontrasting
confidence: 99%
“…The amphetamine (R)/(S) ratios calculated in the sample collective are consistent with the use of racemic amphetamine, taking into account the shorter elimination half-life of (S)-amphetamine [ 28 , 29 ]. The median (R)/(S) ratio in this study was 1.11, which was significantly lower than the median of 1.69 found by Hess et al in a similar study (n = 28) [ 35 ].…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, in a controlled oral intake study by Wan et al (10 mg racemic amphetamine, n = 4), (R)/(S) ratios ranging from 0.84 to 1.18 were observed during the absorption phase [ 29 ]. The occurrence of (R)/(S) ratios below 1.00 is also supported by the studies of Caras and Sharpe, which found higher mean peak serum concentrations of (S)-amphetamine while the times of peak serum concentrations of both enantiomers were similar [ 28 ]. Furthermore, in a study with controlled oral intake of racemic 4-fluoroamphetamine (4-FA), (R)/(S) ratios below 1.00 were observed during the absorption phase (partially even beyond) [ 36 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations